2019
DOI: 10.3390/ijerph16244893
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Cybervictimization: The Role of Direct Confrontation and Resilience on Adolescent Wellbeing

Abstract: Background. Recent studies have consistently identified the negative consequences of cyberbullying on adolescent mental health. Nevertheless, not all cybervictims are alike, and in the last few years some evidence has appeared indicating that faced with cyberbullying, victims may manifest different emotional outcomes. In this study, we explored whether cybervictim resilience fully or partially mediates the effects of cybervictimization and whether a confrontational coping strategy impacts emotional symptoms. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Finally, in line with previous studies [57][58][59]63], the results corroborated Hypothesis 3 and showed that resilience moderated the association between poly-bullying victimization and subjective well-being. However, this relation was very weak and represented only an additional 1% of variance in subjective well-being.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, in line with previous studies [57][58][59]63], the results corroborated Hypothesis 3 and showed that resilience moderated the association between poly-bullying victimization and subjective well-being. However, this relation was very weak and represented only an additional 1% of variance in subjective well-being.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have been conducted to investigate the consequence of cyberbullying, including problems of mental and physical health [3,4,6,15,47]. Nonetheless, the potential mechanisms underlying cyber victimization and psychological and physical symptoms remain unclear, and only little research has explored this specific topic [13,21,22]. The present study is the first to show that internet addiction mediates the relationship between cyber victimization and physical and mental health, and that physical exercise plays a moderating role on the above mediation.…”
Section: Discussionmentioning
confidence: 60%
“…However, only few studies have explored the potential mechanisms underlying the links between cyber victimization and the negative outcomes mentioned above. One study conducted among Italian adolescents found that psychological resilience plays a mediating role between cyber victimization and emotional symptoms [21]. Family dinners were proposed to moderate the relationship between cyber victimization and mental health problems [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, bullying incidents, which are frequent and occur over long periods of time, may overwhelm student's self-efficacy for coping. Improving self-efficacy in dealing with bullying among severely victimized adolescents may foster a crucial protective factor such as resilience [47,48]. As Bandura [49] pointed out, the most powerful work in resilience is promoting personal agency and confidence in one's ability to develop resilience.…”
Section: Discussionmentioning
confidence: 99%